Prebiotic potential of apple pomace and pectins from different apple varieties: Modulatory effects on key target commensal microbial populations - Calvete-Torre, Ines; Sabater, Carlos; Antón, María José; Moreno, F. Javier; Riestra, Sabino; Margolles, Abelardo; Ruiz, Lorena (Food hydrocolloids, 2022)
Pectin is a group of structurally diverse dietary fibers, very abundant in agri-food waste and by-products such as those generated during apple cider manufacturing. In recent years, pectin and pectinoligosaccharides have demonstrated good fermentation properties and prominent health promoting traits, particularly ameliorating certain inflammatory conditions. In previous investigations apple pomace derived from production of monovarietal Asturian ciders was demonstrated to represent a source of pectin with varied structural characteristics. In this work we investigated in vitro the modulatory effect of pectin and pomace fractions derived from the production of selected monovarietal ciders on human microbiota from healthy subjects and inflammatory bowel disease (IBD) patients through fecal batch fermentations and 16S rRNA gene sequencing. Overall, these fractions promoted the growth of Akkermansia, Lachnospiraceae UCG-010, Prevotella, Sucinivibrio and Turicibacter on samples from healthy donors, while Blautia, Lachnospiraceae CAG-56, Dialister, Eubacterium eligens and Intestinimonas were stimulated in fermentations from IBD patients. The growth of Akkermansia, Blautia, E. eligens group, Intestinimonas and Succinivibrio only occurred with pomace and pectin derived from the tested by-products, and not with other non-pectic prebiotics/substrates. Galactose content and (Arabinose + Galactose)/Rhamnose ratio in apple pomace, and galactose and rhamnose content in pectin, were positively associated to the promotion of most of these genera. This work comprehensively characterize the gut microbiota modulation of apple pectin and pomace fractions derived from cider by-products, demonstrating diverse modulatory capacity of structurally distinct pectin and apple pomace fractions. This diversifies the opportunities to achieve cider by-products valorization through formulation of novel prebiotics for particular population groups. [Display omitted] •Apple pomace and pectin modulated beneficial gut bacteria including Eubacterium and Lachnospiraceae in fecal fermentations.•Apple pomace promoted short-chain fatty acid producers in Chron's disease microbiota.•Galactose and rhamnose contents of pectin and apple pomace determine their modulatory activity.•Similar composition-activity relationships were found for apple pomace and pectin.